Quality of Life of Outpatients with Type 2 Diabetes Mellitus at Anutapura Hospital - Diana, Khusnul; Azizah, Vina Miftahul; Hardani, Muhammad Fakhrul; Tandah, Muhamad Rinaldhi (Universitas Muhammadiyah Malang, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease that may reduce health-related quality of life (HRQoL) because of long-term treatment complications. This study assessed HRQoL among T2DM outpatients at Anutapura Hospital and examined whether the overall HRQoL profile differed by medication group after adjustment for selected patient characteristics. A hospital-based cross-sectional study was conducted at the Internal Medicine Outpatient Clinic of Anutapura Hospital, Palu, Indonesia, from October to December 2024. Using non-probability sampling, 92 adults with T2DM were enrolled and classified into three medication groups: monotherapy oral antidiabetic drugs (OADs), combined OADs, and insulin. HRQoL was measured using the Diabetes Quality of Life Clinical Trial Questionnaire-Revised (DQLCTQ-R), which includes eight domains scored on a 0–100 scale, with higher scores indicating better HRQoL. Internal consistency was acceptable (Cronbach’s alpha = 0.82). Because several domains did not meet normality assumptions, the overall HRQoL profile was analyzed using PERMANOVA. Most respondents were female, aged 41–60 years, and had diabetes duration of less than 5 years. Across medication groups, Physical Function showed the highest scores, whereas Treatment Satisfaction tended to be the lowest. In the adjusted PERMANOVA model, medication group was not significantly associated with the overall HRQoL profile (F = 0.81, p = 0.521, R² = 0.014). In contrast, age (p = 0.016), occupation (p = 0.008), and duration of illness (p = 0.001) were significantly associated with the combined HRQoL profile. These findings suggest that HRQoL differences were more strongly related to patient characteristics than to medication group alone.